Anti-corrosive properties of silane coatings deposited on anodised aluminium. (1st December 2016) - Wojciechowski, Jarosław; Szubert, Karol; Peipmann, Ralf; Fritz, Mathias; Schmidt, Udo; Bund, Andreas; Lota, Grzegorz
Graphical abstract: Highlights: Deposits of silane coatings on anodised aluminium oxides inhibit corrosion. Siloxane (Si-O-Si) bonds between silane compounds molecules are formed. Al-O-Si bonds are formed between anodised aluminium oxides and silane coatings. Aluminium oxides with silane coatings have trapped air inside the pores. Abstract: Aluminium anodisation processes were carried out in two different solutions i.e. in oxalic and sulphuric acid. Part of the samples was subjected to hydrothermal sealing in order to seal the pores on the oxide surface. Silane coatings were deposited from two solutions containing triethoxyoctylsilane and tetraethoxysilane. Surface analysis and spectroscopic methods were applied to characterize the pristine and coated samples. Anti-corrosive properties of all samples were assessed using electrochemical methods. It can be concluded that due to the condensation reaction between the anodised aluminium and silane compounds Al-O-Si covalent bonds are created. Fitted equivalent circuit parameters are distinctively different for the investigated systems. Additionally, the size of the particles in colloidal silane solutions was determined. Due to their size the colloidal particles cannot enter into the pores of the oxide layer but form a silane film on top. Thus they create a composite coating containing trapped air in the pores.